The Effects of Halal Certification and Halal Awareness on Purchase Intention of Halal Food Products in Indonesia - Septiani, Devi; Ridlwan, Ahmad Ajib (Indonesian Journal of Halal Research, 2020)
Halal has become part of life worldwide, and the service demand is advancing on a big scale in the industrial and economic frame. This study aims to determine the effects of halal certification and customers' halal awareness of the intention to purchase halal food products. This study belongs to the quantitative type with samples of 105 Muslim respondents. Accidental sampling is applied to sampling data. Four-point Likert scale questionnaire is utilized in data collecting which is analyzed with multiple linear regression techniques using SPSS 23 program. The results of this study indicate that halal certification variables and halal awareness both partially have positive effects on purchase intentions of halal food products. Meanwhile, the two variables simultaneously, halal certification and halal awareness, also positively influence the intention to purchase halal food products.